A method for producing high purity polydextrose

CN122940919APending Publication Date: 2026-10-20DANISCO SWEETENERS (ANYANG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611254405.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]随着市场对高端产品的需求提升,传统聚葡萄糖制备工艺存在的缺陷日益凸显:一是产品纯度不足,残留的葡萄糖、山梨醇等杂质导致还原糖含量偏高,影响产品稳定性,无法实现“无糖”特性,限制了在低糖、无糖食品中的应用;二是工艺收率有限,分离过程中部分有效成分浪费,且无循环利用机制;三是纯化步骤简单,离子残留、色素等问题难以彻底解决

Benefits of technology

[0016]本申请以葡萄糖和山梨醇为原料,经聚合、稀释、脱色、离子交换、色谱分离、浓缩、氢化、多级纯化及喷粉等步骤完成,解决传统方法纯度低、收率有限、杂质残留及无法循环利用的问题,所得产品纯度高、几乎无还原糖残留,且工艺绿色环保、收率提升显著,具备工业化推广价值。具体而言,通过“色谱分离+AD提余液回套+氢化反应+多级纯化”组合工艺,产品纯度≥99.6%,还原糖残留趋近于0.1%,完全满足无糖产品要求;AD提余液回套至聚合工序,避免有效成分浪费,总收率较传统工艺提高10-15%,可达87%以上,同时AD提余液循环利用减少废液排放,符合工业化绿色生产要求;经多级离子交换控制,尤其喷粉前料液经混床离子交换工序进行处理,电导率≤20μs/cm,保证产品pH稳定在5-6,色素及离子残留极低,降低产品的酸性或碱性降解,从而稳定成品还原糖含量和色度,产品储存期延长;各步骤参数明确,操作简单,适配规模化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention belongs to the field of polydextrose synthesis and purification technology, and provides a method for producing high-purity polydextrose, including the following steps: S1, adding citric acid and purified water to glucose and sorbitol to carry out a polymerization reaction; S2, diluting the reaction solution; S3, decolorizing the diluted solution; S4, treating the decolorized solution first with a cation exchange resin and then with an anion exchange resin; S5, chromatographically purifying the ion exchange solution obtained in S4, collecting the front-end BD extract, recovering the back-end AD residue, and returning the AD residue to the polymerization step in S1; S6, concentrating the BD extract; S7, hydrogenating the concentrated solution; S8, filtering the hydrogenated solution; S9, decolorizing the filtrate; S10, treating the decolorized solution sequentially with a cation exchange resin, anion exchange resin, and mixed-bed exchange resin; S11, concentrating the ion exchange solution; S12, spray-drying the concentrated solution. This application solves the problems of low purity, limited yield, residual impurities, and inability to recycle in traditional methods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polydextrose synthesis and purification technology, and in particular relates to a method for producing high-purity polydextrose. Background Technology

[0002] Polydextrose, a functional low-calorie carbohydrate, possesses properties such as low sweetness, low calories, and the ability to regulate gut microbiota, and has been widely used in the food and health product industries. Physiologically, it is not easily digested and absorbed by the human body, with only about 1 kcal / g, allowing it to replace some sugar sources and reduce calorie intake. Its low glycemic index helps slow the rise in blood sugar, making it suitable for diabetics and those controlling their blood sugar. Simultaneously, it can serve as a fermentation substrate for beneficial gut bacteria, regulating gut microbiota balance, promoting intestinal motility, and preventing constipation. In food applications, it combines thickening, stabilizing, and water-holding properties, improving food texture and taste, and is widely used in the processing of beverages, pastries, and dairy products. Furthermore, it enhances satiety, aids in weight management, and does not affect mineral absorption and utilization, making it a functional ingredient with both nutritional value and processing suitability.

[0003] As market demand for high-end products increases, the shortcomings of traditional polydextrose preparation processes are becoming increasingly apparent: First, the product purity is insufficient, with residual glucose, sorbitol and other impurities leading to high reducing sugar content, affecting product stability and making it impossible to achieve the "sugar-free" characteristic, thus limiting its application in low-sugar and sugar-free foods; second, the process yield is limited, with some effective components wasted during separation and no recycling mechanism; and third, the purification steps are simple, making it difficult to completely solve problems such as ion residues and pigments.

[0004] While existing technologies employ purification methods such as hydrogenation and chromatographic separation of purified polydextrose, they lack a cyclical design of "front-end separation - back-end recirculation" and fail to thoroughly remove reducing sugars through chromatographic separation followed by hydrogenation, resulting in products that do not meet sugar-free standards. Therefore, developing a polydextrose preparation method that combines high purity, sugar-free properties, high yield, and environmental friendliness has become a pressing issue for the industry. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention optimizes the process route, designs a recycling mechanism, and implements multi-stage purification steps to achieve the goals of improving product purity, meeting sugar-free characteristics, increasing yield, and efficiently removing impurities.

[0006] This invention provides a method for producing high-purity polydextrose, comprising the following steps: S1. Glucose and sorbitol are used as raw materials, citric acid and purified water are added, and a polymerization reaction is carried out under high temperature and vacuum conditions to obtain a molten polymer. S2. Add purified water to the melted polymer obtained in S1 to dilute it and obtain a diluted solution; S3. Decolorize the diluted solution obtained in S2 using activated carbon. S4. The decolorized liquid is first treated with a cation exchange resin to remove metal ions, and then treated with an anion exchange resin to remove acid radical ions, etc., to obtain an ion exchange solution. S5. Perform chromatographic two-component purification on the ion exchange liquid obtained in S4, collect the BD extract containing polydextrose at the front end, and recover the AD residue containing glucose and sorbitol at the back end (containing incompletely separated effective components, including glucose and sorbitol). Return the AD residue to the polymerization process in S1 to achieve resource recycling and improve the overall yield. S6. Concentrate the BD extract collected in S5 to obtain a concentrated solution; S7. Adjust the pH of the concentrated solution obtained in S6 to 6-8 and carry out the hydrogenation reaction; S8. Filter the hydrogenated liquid obtained in S7 using a ceramic membrane. S9. The ceramic membrane filtrate obtained in S8 is decolorized with granular carbon. The granular carbon adsorbs residual pigments and hydrogenation reaction byproducts, further improving the color purity of the product. S10. The decolorized solution obtained in S9 is sequentially treated with cation exchange resin, anion exchange resin, and mixed bed exchange resin. The purpose of mixed bed ion exchange is to stabilize the pH of the exchange solution. S11. Concentrate the ion exchange solution obtained in S10; S12. The concentrated liquid obtained in S11 is sprayed through a spray tower to obtain a high-purity polydextrose product. After spraying through the spray tower, a white powdery high-purity polydextrose product with sugar-free properties is obtained.

[0007] More preferably, in step S1, the molar ratio of glucose to sorbitol is 1.0:0.15-0.20, the mass of citric acid added is 0.01-0.02% of the total mass of the raw materials, and the mass of purified water added is 10-15% of the total mass of the raw materials; the high-temperature vacuum conditions in step S1 are: temperature 130-180℃, vacuum degree 0.02~0.06MPa, and polymerization reaction time 2-6h. The precise proportioning of raw materials and accurate control of polymerization reaction conditions in this application ensures a complete polymerization reaction and reduces the formation of by-products.

[0008] More preferably, the concentration of the diluent in step S2 is 50-60% to provide a suitable system viscosity for subsequent decolorization and ion exchange.

[0009] More preferably, in step S3, activated carbon is added at 0.3-1.0% of the mass of the diluted solution, and the mixture is stirred and decolorized at 50-70°C for 30-40 minutes to reliably adsorb pigments and some organic impurities in the system.

[0010] More preferably, in step S4, the conductivity of the ion exchange solution is controlled to be ≤20 μs / cm to reduce contamination of the chromatographic resin.

[0011] More preferably, in step S5, the chromatographic purification uses a cation exchange resin, the column temperature is controlled at 65℃, the resin throughput is 0.02 kg / (L·h), the eluent is deionized water, the raw material concentration is 50-60%, the water-to-material mass ratio is 2.4-3:1, and the output mass ratio is BD / AD = 0.5-1:1. By precisely controlling the chromatographic parameters, a balance between separation efficiency and purity can be ensured.

[0012] More preferably, in step S6, the BD extract is concentrated to a concentration of 40-45% to meet the system requirements of the subsequent hydrogenation reaction; the hydrogenation reaction conditions in step S7 are: reaction temperature 100-130℃, reaction pressure 3-5MPa, and reaction time 2-3h, to convert residual reducing sugars into polyols as much as possible and achieve the sugar-free characteristics of the product; wherein, the catalyst is Raney nickel, and the amount of catalyst added is 5-10% of the mass of the concentrate in step S6.

[0013] More preferably, in step S8, the ceramic membrane has a pore size of 0.1-0.2 μm and a filtration pressure of 0.3-0.5 MPa to ensure the removal of catalyst particles and trace suspended matter.

[0014] More preferably, in step S10, the mixed-bed ion exchange resin is made by uniformly mixing macroporous strong-basic anion exchange resin and macroporous strong-acidic cation exchange resin at a volume ratio of 1.5-2:1, with a feed temperature of 40℃ and a feed rate of 1-2 BV / h. The anti-fouling ability of the macroporous resin supports long-term stability under low-speed operation, avoiding bed compaction or microbial growth caused by excessively slow flow rate. The macroporous resin provides physical protection, and the asymmetric ratio of macroporous strong-basic anion exchange resin and macroporous strong-acidic cation exchange resin achieves chemical equilibrium. Temperature control can reduce the viscosity of the feed solution and accelerate the ion diffusion rate. The low speed extends the residence time of the feed solution in the resin bed, allowing sufficient time for trace amounts of residual metal cations and anions to complete the entire process of "membrane diffusion-particle diffusion-exchange" under the support of "macroporous structure + temperature rise", thereby ensuring extremely low pigment and ion residues.

[0015] More preferably, in step S11, the concentration is carried out under vacuum, with a concentration temperature of 60-70℃ and a vacuum degree of 0.08-0.095MPa, to concentrate the ion exchange solution obtained in S10 to a concentration of 50-55%, which can prepare it for spraying.

[0016] This application uses glucose and sorbitol as raw materials, and completes the process through steps such as polymerization, dilution, decolorization, ion exchange, chromatographic separation, concentration, hydrogenation, multi-stage purification and spray drying. It solves the problems of low purity, limited yield, impurity residue and inability to recycle in traditional methods. The resulting product has high purity and almost no reducing sugar residue. Moreover, the process is green and environmentally friendly, and the yield is significantly improved, making it valuable for industrial promotion. Specifically, through a combined process of "chromatographic separation + AD residue recycling + hydrogenation reaction + multi-stage purification," the product purity is ≥99.6%, and the reducing sugar residue is close to 0.1%, fully meeting the requirements for sugar-free products. The AD residue is recycled to the polymerization process, avoiding waste of effective components. The overall yield is 10-15% higher than that of traditional processes, reaching over 87%. At the same time, the recycling of the AD residue reduces waste liquid discharge, meeting the requirements of industrial green production. Through multi-stage ion exchange control, especially the pre-powdering liquid treated by a mixed-bed ion exchange process, the conductivity is ≤20μs / cm, ensuring that the product pH is stable at 5-6, with extremely low pigment and ion residues, reducing acidic or alkaline degradation of the product, thereby stabilizing the reducing sugar content and color of the finished product and extending the product's shelf life. The parameters of each step are clearly defined, the operation is simple, and it is suitable for large-scale production.

[0017] In this application, the ion exchange solution obtained in S4 is first purified by two-component chromatographic extraction, and then the concentrated solution obtained in S6 is adjusted to pH 6-8 for hydrogenation. This process purifies the polymerization solution before hydrogenation to reduce reducing sugars. The hydrogenation process does not generate large amounts of sugar alcohol byproducts, thus improving the purity of the final product. If the process is changed to hydrogenation followed by chromatography, not only will the product purity decrease and the reducing sugar content increase, but the AD residue from chromatographic separation cannot be directly recycled. This is because: the hydrogenated material must undergo sequential wet-heat processes such as chromatographic separation and concentration; residual trace ions in the system will catalyze the hydrolysis of polydextrose glycosidic bonds, further increasing the reducing sugar content; the polymerization solution contains numerous impurities, and direct hydrogenation without purification will generate large amounts of sugar alcohol byproducts that are difficult to remove in subsequent chromatography, leading to decreased product purity; direct hydrogenation of the polymerization solution increases the content of heteroglycol alcohols, which will also affect the direct reuse of the AD residue, increasing production costs. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a schematic diagram of the process flow for a method of producing high-purity polydextrose provided by the present invention. Detailed Implementation

[0020] The following will be combined with the appendix Figure 1 Specific embodiments and comparative examples clearly and completely describe the technical solutions of the present invention. However, those skilled in the art should understand that the embodiments are only used to illustrate the technical solutions of the present invention and should not be regarded as limiting the scope of protection of the present invention. Based on the following embodiments, all other implementation schemes obtained by those skilled in the art without creative effort, such as implementation schemes obtained by modification, variation or simple substitution, should fall within the scope of protection of the present invention.

[0021] Example 1 S1. Weigh out the raw materials, including glucose and sorbitol in a molar ratio of 1.0:0.18, add 0.015% citric acid and 12% deionized water by mass of the raw materials, and put them into a vacuum polymerization reactor. Polymerize at 132℃ and -0.06MPa for 5 hours to obtain a molten polymer with a polydextrose purity of 91.7% and a reducing sugar content of 0.58%. S2. Add purified water to the polymer and stir to dilute to a concentration of 55%. S3. Add 0.8% activated carbon by weight of the diluent, decolorize at 65℃ for 35 min, and remove activated carbon by plate and frame filtration; S4. The filtrate was first treated with cation exchange resin and then with anion exchange resin. The conductivity of the ion exchange solution was measured to be 18 μs / cm. S5. Separation was performed using a cation exchange column at 65℃. The resin throughput was 0.02 kg / (L·h), and the eluent (purified water) volume was 2.4 times the feed mass. The BD extract containing polydextrose at the front end and the AD retentate containing glucose and sorbitol at the back end were collected, concentrated, and stored for later use. The purity of polydextrose in the BD extract was 99.5%, and the reducing sugar content was 0.35%. S6. Concentrate the BD extract to a concentration of 42% at 65℃ and -0.09MPa. S7. Adjust the pH of the concentrate to 8.0 with 10% sodium hydroxide solution, add 5.0% Raney nickel catalyst (by mass of the concentrate), and hydrogenate at 105℃ and 4MPa for 2.5h. The polydextrose purity is 99.6%, and the reducing sugar content is 0.05%. S8. A 0.15μm ceramic membrane is used to filter the hydrogenation liquid under a pressure of 0.4MPa to remove the catalyst; S9. Add 0.5% of the filtrate mass of granular activated carbon, decolorize at 60℃ for 20 min, and filter to remove granular activated carbon. S10. The decolorized solution was treated sequentially with cation exchange resin, anion exchange resin, and mixed bed exchange resin. The pH was measured to be 5.5 and the conductivity to be 15 μs / cm. S11, Concentrate to 52% concentration at 65℃ and -0.09MPa; S12. The concentrate is fed into the spray tower, and the inlet air temperature is controlled at 180℃ and the outlet air temperature at 80℃. High-purity sugar-free polydextrose product is obtained by spraying.

[0022] The product was tested and found to have a purity of 99.72%, a reducing sugar content of 0.08%, and a yield of 85.3%.

[0023] Example 2 The AD residue recovered in S5 of Example 1 was calculated by dry weight, converted to the ratio of glucose to sorbitol, and then recycled back to the polymerization step in S1. The remaining steps were the same as in Example 1. Testing showed that the product purity was 99.68%, the reducing sugar content was 0.09%, the yield was 98.1%, and all product indicators were stable.

[0024] Example 3 S1. Glucose and sorbitol were weighed out at a molar ratio of 1.0:0.15. Citric acid (0.016% of the total raw material mass) and deionized water (15% of the total raw material mass) were added, and the mixture was placed in a vacuum polymerization reactor. Polymerization was carried out at 172℃ and -0.06MPa for 3 hours to obtain a molten polymer. The polydextrose purity was 92.3%, and the reducing sugar content was 0.63%. S2. Add purified water to the polymer and stir to dilute to a concentration of 54%. S3. Add 0.6% activated carbon by weight of the diluent, decolorize at 65℃ for 30 min, and remove activated carbon by plate and frame filtration; S4. The filtrate was first treated with cation exchange resin and then with anion exchange resin. The conductivity of the ion exchange solution was measured to be 12 μs / cm. S5. Separation was performed using a cation exchange column at 65℃. The resin throughput was 0.02 kg / (L·h), and the eluent (purified water) volume was 2.6 times the feed mass. The BD extract was collected from the front end, and the AD retentate was stored for later use. The polydextrose purity in the BD extract was 99.4%, and the reducing sugar content was 0.39%. S6. Concentrate the BD extract to a concentration of 43% at 67℃ and -0.095MPa. S7. Adjust the pH of the concentrate to 7.2 with 10% sodium hydroxide solution, add 5.0% Raney nickel catalyst (by mass of the concentrate), and hydrogenate at 110℃ and 4MPa for 2 hours. The polydextrose purity is 99.45%, and the reducing sugar content is 0.04%. S8. A 0.1μm ceramic membrane is used to filter the hydrogenation liquid under a pressure of 0.4MPa to remove the catalyst; S9. The hydrogenated liquid in S8 is treated with granular carbon at a feed rate of 1-2 BV / h. S10. The decolorized solution was treated sequentially with cation exchange resin, anion exchange resin, and mixed bed exchange resin. The pH was measured to be 5.2 and the conductivity to be 11 μs / cm. S11, concentrated to 53% concentration at 65℃ and -0.09MPa; S12. The concentrate is fed into the spray tower, and the inlet air temperature is controlled at 180℃ and the outlet air temperature at 80℃. High-purity sugar-free polydextrose product is obtained by spraying.

[0025] The product was tested and found to have a purity of 99.66%, a reducing sugar content of 0.07%, and a yield of 88.3%.

[0026] Example 4 The AD residue recovered in S5 of Example 3 was calculated by dry weight, converted to the ratio of glucose to sorbitol, and then recycled back to the polymerization step in S1. The remaining steps were the same as in Example 3. Testing showed that the product purity was 99.81%, the reducing sugar content was 0.07%, the yield was 97.2%, and all product indicators were stable.

[0027] The present invention has verified the feasibility and stability of the process through the above specific embodiments. The parameter details can be adjusted according to actual production needs, and the technical effects of the present invention can be achieved.

[0028] Comparative Example 1 Based on Example 1, only the order of chromatographic separation and hydrogenation reduction was interchanged, while other control parameters remained the same. The resulting polydextrose product had a purity of 97.6%, a reducing sugar content of 0.27%, and a yield of 85.3%. Furthermore, the AD residue from chromatographic separation contained impurities other than sorbitol, making direct recovery and reuse impossible. The reason for the decrease in product purity and increase in reducing sugar content in Comparative Example 1 (where the process was changed to hydrogenation followed by chromatography) is as follows: the hydrogenated material requires sequential chromatographic separation and concentration under wet heat, and residual trace ions in the system catalyze the hydrolysis of polydextrose glycosidic bonds, leading to a further increase in reducing sugar content; the polymerization solution contains numerous impurities, and direct hydrogenation without purification generates a large amount of sugar alcohol byproducts that are difficult to remove in subsequent chromatography, resulting in decreased product purity; direct hydrogenation of the polymerization solution increases the content of heteroglycol alcohols, which also affects the direct reuse of the AD residue, increasing production costs.

[0029] Comparative Example 2 Based on Example 1, only the mixed-bed ion exchange in S10 is omitted, that is, after anion exchange, the product is directly concentrated and sprayed with powder. The pH index and reducing sugar of the same batch of products stored for different time periods vary too much, resulting in unstable product quality.

[0030] The product from Implementation Case 1 and a randomly selected product from Comparative Example 2 were placed in a stability chamber at 40°C and 75% humidity for stability testing. The test data are as follows: The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0031] The mechanism provided by this invention has been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this invention. The descriptions of the embodiments above are only intended to help understand the method and core ideas of this invention. It should be noted that those skilled in the art can make various improvements and modifications to this invention without departing from its principles, and these improvements and modifications also fall within the protection scope of the claims of this invention. Therefore, this invention is not limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for producing high-purity polydextrose, characterized in that, Includes the following steps: S1. Glucose and sorbitol are used as raw materials, citric acid and purified water are added, and a polymerization reaction is carried out under high temperature and vacuum conditions to obtain a molten polymer. S2. Add purified water to the melted polymer obtained in S1 to dilute it and obtain a diluted solution; S3. Decolorize the diluted solution obtained in S2 using activated carbon. S4. The decolorized liquid is first treated with a cation exchange resin, and then with an anion exchange resin to obtain an ion exchange solution. S5. Perform chromatographic two-component purification on the ion exchange liquid obtained in S4, collect the BD extract containing polydextrose at the front end, recover the AD residue containing glucose and sorbitol at the back end, and return the AD residue to the polymerization step in S1. S6. Concentrate the BD extract collected in S5 to obtain a concentrated solution; S7. Adjust the pH of the concentrated solution obtained in S6 to 6-8 and carry out the hydrogenation reaction; S8. Filter the hydrogenated liquid obtained in S7 using a ceramic membrane. S9. The ceramic membrane filtrate obtained in S8 is decolorized with granular carbon. S10. The decolorized liquid obtained in S9 is sequentially treated with cation exchange resin, anion exchange resin, and mixed bed exchange resin. The pH of the treated liquid is controlled between 5 and 6, and the conductivity is ≤20μs / cm. S11. Concentrate the ion exchange solution obtained in S10; S12. The concentrated liquid obtained in S11 is sprayed into powder through a spray tower to obtain a high-purity polydextrose product.

2. The method for producing high-purity polydextrose according to claim 1, characterized in that, In step S1, the molar ratio of glucose to sorbitol is 1.0:0.15-0.20, the mass of citric acid added is 0.01-0.02% of the total mass of raw materials, and the mass of purified water added is 10-15% of the total mass of raw materials. The high-temperature vacuum conditions in step S1 are: temperature 130-180℃, vacuum degree 0.02~0.06MPa, and polymerization reaction time 2-6h.

3. The method for producing high-purity polydextrose according to claim 1, characterized in that, The concentration of the diluent in step S2 is 50-60%.

4. The method for producing high-purity polydextrose according to claim 1, characterized in that, In step S3, activated carbon is added at 0.3-1.0% of the mass of the diluted solution, and the mixture is stirred and decolorized at 50-70°C for 30-40 minutes.

5. The method for producing high-purity polydextrose according to claim 1, characterized in that, In step S4, the conductivity of the ion exchange solution is controlled to be ≤20 μs / cm.

6. The method for producing high-purity polydextrose according to claim 1, characterized in that, In step S5, chromatographic purification uses cation exchange resin, the column temperature is controlled at 65℃, the resin throughput is 0.02 kg / (L·h), the eluent is deionized water, the raw material concentration is 50-60%, the water-to-material mass ratio is 2.4-3:1, and the output mass ratio is BD / AD=0.5-1:

1.

7. The method for producing high-purity polydextrose according to claim 1, characterized in that, In step S6, the BD extract is concentrated to a concentration of 40-45%; in step S7, the hydrogenation reaction conditions are: reaction temperature 100-130℃, reaction pressure 3-5MPa, reaction time 2-3h, the catalyst is Raney nickel, and the amount of catalyst added is 5-10% of the mass of the concentrate in step S6.

8. The method for producing high-purity polydextrose according to claim 1, characterized in that, In step S8, the ceramic membrane has a pore size of 0.1-0.2 μm and a filtration pressure of 0.3-0.5 MPa.

9. The method for producing high-purity polydextrose according to claim 1, characterized in that, In step S10, the mixed-bed ion exchange resin is made by mixing macroporous strong basic anion exchange resin and macroporous strong acid cation exchange resin at a volume ratio of 1.5-2:

1. The material flow temperature is 40℃ and the material flow rate is 1-2 BV / h.

10. A method for producing high-purity polydextrose according to claim 1, characterized in that, In step S11, the concentration is carried out under vacuum, with a concentration temperature of 60-70℃ and a vacuum degree of 0.08-0.095MPa, to concentrate the ion exchange solution obtained in S10 to a concentration of 50-55%.